Characterisation, evaluation and use of non-Saccharomyces yeast strains isolated from vineyards and must - Jolly, N. P. (Neil Paul) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2004.